Phase I study of the safety and clinical activity of the interleukin-8 inhibitor AMY109 combined with atezolizumab in patients with advanced solid cancers - Yasutoshi Kuboki; Masafumi Ikeda; Shigehisa Kitano; Takafumi Koyama; Noboru Yamamoto; Yuki Yamaguchi; Yuki Nakagawa; Takaaki Ishida; Hidenori Mizugaki; Takatsugu Narikiyo; Ryoko Takubo; Chika Ogami; et al. (Journal for ImmunoTherapy of Cancer)
Background Immunosuppressive conditions within the tumor microenvironment (TME) can allow tumors to evade the immune system, including by hampering programmed death ligand 1 (PD-L1) inhibitor activity. Interleukin (IL)-8 contributes to immunosuppression and fibrosis in the TME. AMY109, a humanized anti-IL-8 monoclonal antibody, reduced fibrosis and decreased immunosuppressive cells in tumor tissue in animals. Combining AMY109 with atezolizumab (anti-PD-L1 antibody) may enhance its antitumor effects by making the TME more favorable to PD-L1 inhibition.Methods This multicenter, open-label, dose-escalation study evaluated the safety, pharmacokinetics, and clinical activity of AMY109 plus atezolizumab in patients with previously treated advanced solid tumors and Eastern Cooperative Oncology Group performance status 0 or 1. Patients received AMY109 (2–45 mg/kg) plus atezolizumab (1200 mg) intravenously every 3 weeks in part 1, and AMY109 (15–45 mg/kg) plus atezolizumab (1200 mg) in part 2. Primary endpoints were the dose-limiting toxicity (DLT), safety, and pharmacokinetics of AMY109 and atezolizumab in Part 1, and safety and antitumor activity per investigator-assessed Response Evaluation Criteria in Solid Tumors 1.1 in part 2. Exploratory analyses of peripheral and tumor biomarker were conducted.Results Overall, 38 patients (18 in part 1 and 20 in part 2) were enrolled. Part 1 showed no DLTs and a dose-proportional increase in AMY109 exposure over 2–45 mg/kg, with no apparent change in mean atezolizumab serum concentrations across AMY109 dosing. Plasma IL-8 concentration accumulation was seen in all dose cohorts after AMY109 initiation. Grade 1–3 treatment-related adverse events (AEs) occurred in 21 of 38 patients (55%). Treatment-related serious AEs occurred in two patients (5%). No AEs led to treatment withdrawal. Partial responses (PRs) occurred in 2 of 38 patients; the confirmed objective response rate was 5%. These patients had uterocervical and pancreatic cancer, respectively, and had been treated for >500 days at the cut-off date: one had received 45 mg/kg of AMY109 throughout, and the other received 30 mg/kg of AMY109 until cycle 5, then 45 mg/kg thereafter.Conclusions With no DLTs, AMY109 plus atezolizumab was well tolerated in patients with advanced solid tumors, with no new safety signals. AMY109 showed a dose-proportional increase in exposure. The PRs in two patients were durable.